The Response and Recovery of Carbon and Water Fluxes in Australian Ecosystems Exposed to Severe Drought - C. Stephens; B. Medlyn; L. Williams; J. Knauer; A. Inbar; E. Pendall; S. K. Arndt; J. Beringer; C. M. Ewenz; N. Hinko‐Najera; L. B. Hutley; P. Isaac; et al. (Global Change Biology, 2025)
Climate change‐driven increases in drought risk pose a critical threat to global carbon and water cycles. However, ecosystem‐scale responses remain poorly quantified, particularly for severe, multiyear drought events. We addressed this gap by examining ecosystem‐scale carbon and water flux sensitivity to the extreme 2018–19 drought in Australia using data from 14 eddy covariance flux sites. The ecosystems span grasslands and semi‐arid woodlands to tropical and temperate forests. The driest sites (classed as “grass” and “very dry”) experienced drastic productivity impacts, with a 65% decrease in Gross Primary Productivity (GPP) over 2 years relative to the pre‐drought average. However, fluxes in “dry,” “seasonally wet” and “wet” ecosystems showed remarkable resistance, with no overall change in GPP. All sites recovered rapidly; carbon fluxes in the first post‐drought year matched (and generally exceeded) those of a climatically similar pre‐drought year. Drought responses were strongly mediated by ecosystem‐specific strategies. The driest ecosystems showed direct coupling of productivity to water availability, while intermediate ecosystems (dry and seasonally wet) leveraged stored soil water to maintain evapotranspiration and productivity under drought. At these sites, water was conserved over wet periods (evapotranspiration rainfall). This mechanism mitigating periodic water stress under high rainfall variability likely contributed to the notable drought resistance of the dry and seasonally wet sites. The monthly water deficit index (MWDI) emerged as a robust predictor of productivity across space, highlighting that short‐term water availability deficits strongly influence overall ecosystem composition. Analysis of drought response mechanisms suggested rapid leaf loss under water stress, particularly at the driest sites. Our findings underscore the importance of accounting for sub‐surface water storage and diverse drought response strategies in vegetation models. We provide critical benchmarks for improving parameterization of plant‐water relations, aiding efforts to inform climate‐robust management strategies.

Engaging high-school students in scientific conferences - Dorrit Inbar; Yonatan M. Kupchik; Danny Ben-Zvi; Yossi Yovel; Irit Sadeh (Trends in Ecology & Evolution, 2024)

Cryopreservation of Anopheles stephensi (MOSQUITO) EGGS: EFFECTS ON GENOTYPIC AND PHENOTYPIC CHARACTERISTICS - Morgan Douglas; Ehud Inbar; Igor Sharakov; Najib M. El-Sayed; Ashton T. Belew; James Overby; Steve Matheny; Fantahun Addisu; Yonas Abebe; Dimitri Koutzoumis; Kerri Springer; Abraham Eappen; et al. (Cryobiology, 2023)

Plant cell piercing by a predatory mite: evidence and implications - E. Adar; M. Inbar; S. Gal; L. Issman; E. Palevsky (Experimental and Applied Acarology, 2015)

Conspicuous gall colors: a response to T. C. R. White - M. Inbar; I. Izhaki; A. Koplovich; I. Lupo; N. Silanikove; T. Glasser; Y. Gerchman; A. Perevolotsky; S. Lev-Yadun (Arthropod-Plant Interactions, 2010)

Why do many galls have conspicuous colors? A new hypothesis - M. Inbar; I. Izhaki; A. Koplovich; I. Lupo; N. Silanikove; T. Glasser; Y. Gerchman; A. Perevolotsky; S. Lev-Yadun (Arthropod-Plant Interactions, 2010)

Estimation of muscle spindle information rate by pattern matching and the effect of gamma system activity on parallel spindles - Y Tock; G.F Inbar; Y Steinberg; M Ljubisavljevic; J Thunberg; U Windhorst; H Johansson (Biological Cybernetics, 2005)

Abstracts of Presentations at the 18th Conference of the Entomological Society of Israel - M. P. Pener; L. Anshelevich; E. Dunkelblum; M. Hard; A. Harari; D. Gordon; M. Kehat; H. Reuveny; O. Akunis; D. Oppenheim; E. Dunkelblum; Acta Rafaeli; et al. (Phytoparasitica, 2001)

Unilateral Vocal Cord Paralysis as a Result of a Nocardia farcinica Laryngeal Abscess - E. Cohen; D. Blickstein; E. Inbar; Z. Samra; M. Weinberger (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Leaching of Terbuthylazine and Bromacil Through Field Soils - Inbar Toiber-Yasur; M. Rosner; Aviva Hadas; D. Russo; B. Yaron (Water, Air, & Soil Pollution, 1999)

Elicitors of Plant Defensive Systems Reduce Insect Densities and Disease Incidence - Moshe Inbar; Hamed Doostdar; Ronald M. Sonoda; Gary L. Leibee; Richard T. Mayer (Journal of Chemical Ecology, 1998)

Unsaturated free fatty acids inactivate animal enveloped viruses - A. Kohn; J. Gitelman; M. Inbar (Archives of Virology, 1980)

Fluorescence polarization of DPH-labeled cells adsorbing viruses and its diagnostic potential - A. Levanon; M. Inbar; A. Kohn (Archives of Virology, 1979)